A comparative evaluation of state-of-the-art integration testing techniques of component-based software - Abubakar, Elsafi (Asian Research Publishing Network (ARPN), 2015)
In the last few years, component-based software has gained widespread notice and acceptance as a method that facilitates the development of existing large, complex, and very critical systems by integrating prefabricated small pieces of software called components. Component integration becomes an essential stage in the component-based software development Lifecycle. Therefore, testing components after integration is an important activity. Due to the unavailability of source code of integrated components and due to the lack of component information or documentations, integration testing becomes more difficult and very complex task. In the literature, different techniques have been proposed with the purpose of facilitating the integration testing of component-based software. In this paper, we study, classify, and evaluate some of the existing integration testing techniques and make a comparison in order to help in develop new, better and more efficient and effective techniques for integration testing of component-based software systems.